DIPG-74. DNA METHYLATION STOCHASTICITY IN DIPG. Issue 2 (22nd June 2018) - Koldobskiy, Michael; Jenkinson, Garrett; Pujadas, Elisabet; Martin, Allison; Eberhart, Charles; Goutsias, John; Raabe, Eric; Feinberg, Andrew
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a childhood brainstem tumor with a dismal prognosis and no effective treatment. Recent studies point to a critical role for epigenetic dysregulation in this disease. Nearly 80% of DIPGs harbor mutations in histone H3 encoding replacement of lysine 27 with methionine (K27M), leading to global loss of the repressive histone H3K27 trimethylation mark, global DNA hypomethylation, and a unique gene expression profile. Recent studies across diverse cancers have highlighted the role of epigenetic variability as a driving force in tumor evolution. Epigenetic variability may underlie the heterogeneity and phenotypic plasticity of cancer cells and allow for the selection of cellular traits that promote survival and resistance to therapy. Our group has recently described a novel mathematical framework for analyzing variability of DNA methylation directly from whole-genome bisulfite sequencing data by modeling stochastic Markov processes, allowing rigorous computation of DNA methylation entropy at precise genomic locations. We have carried out genome-wide characterization of DNA methylation at single-base resolution in DIPG in order to generate comprehensive genome-wide maps of DNA methylation entropy. We find a global increase in DNA methylation entropy in DIPG. Dissection of the targets of this perturbation highlights specific genes and regulatory regions under epigenetic control in DIPG cells. We assess the effect of pharmacologic DNA methyltransferase inhibition on the DNA methylation landscape and on gene expression in DIPG patient-derived neurosphere cell lines. We find that DNA methyltransferase inhibition alters expression of genes involved in cell death, differentiation, cellular defense, and immune signaling.